A randomized study of endobronchial valves for advanced emphysema - Sciurba, Frank; Ernst, Armin; Herth, Felix; Strange, Charlie; Criner, Gerard J.; Marquette, Charles H.; Kovitz, Kevin L.; Chiacchierini, Richard P.; Goldin, Jonathan; McLennan, Geoffrey (The New England journal of medicine, 2010)
Endobronchial valves that allow air to escape from a pulmonary lobe but not enter it can induce a reduction in lobar volume that may thereby improve lung function and exercise tolerance in patients with pulmonary hyperinflation related to advanced emphysema. We compared the safety and efficacy of endobronchial-valve therapy in patients with heterogeneous emphysema versus standard medical care. Efficacy end points were percent changes in the forced expiratory volume in 1 second (FEV1) and the 6-minute walk test on intention-to-treat analysis. We assessed safety on the basis of the rate of a composite of six major complications.
Gesehen am 12.07.2023